Analisis Konseptual Perbandingan Media Konvensional Dan Digital Terhadap Hasil Belajar Pai: Perspektif Teori Behaviorisme Skinner Dan Pendidikan Islam - Muslimin; Ahdar; Haq, Islamul; Halik, Abdul; Halik, Muzakkir (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This conceptual analysis addresses the challenges in Islamic Religious Education learning outcomes amid the digital era transition, where conventional media like face-to-face lectures and printed books struggle with passive engagement, while digital tools such as interactive videos and online platforms enhance interactivity but risk distractions and motivational decline. The objective is to compare these media through the lens of Skinner's behaviorism theory and Islamic education principles to propose an integrative hybrid model for holistic improvement. Employing a qualitative conceptual approach via library research and thematic synthesis of primary sources like Skinner's works and Quranic texts alongside secondary literature from 2010-2025, the study reveals that digital media boosts cognitive and behavioral outcomes by up to 40% through multimodal stimuli and variable reinforcement, complemented by Islamic principles like tawhid for intrinsic motivation, reducing disengagement by 30-45%. The hybrid model, blending 60% digital reinforcement with 40% conventional reflection, yields a projected 50% holistic gain across cognitive, affective, and psychomotor domains. In conclusion, this integration fosters resilient spiritual-behavioral development, urging educators to adopt adaptive strategies for inclusive Islamic education.